2020
DOI: 10.2166/ws.2020.145
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum operational conditions for the removal of 2-MIB from drinking water by peroxone process: a pilot-scale study

Abstract: Abstract Taste and odor in drinking water are one of the main problems of water supply and treatment sector. Peroxone is an effective advanced oxidation process, which combines ozone with hydrogen peroxide to create hydroxyl radicals that decompose organic compounds. 2-Methylisoborneol (2-MIB) is one of the significant taste and odor causing compounds, which can be removed with peroxone process. In this study, removal of 2-MIB compound by peroxone process was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As for low NOM-containing ones, the greater the ratio, the better the obtained results (the ratio in the range of 0–0.5) . Considering the problem of residual H 2 O 2 which is recommended to remain lower than 0.5 mg L –1 , Fakioglu et al suggested that the optimal ratio of H 2 O 2 /O 3 was about 0.3 …”
Section: Removal Efficiency Of Odor Compounds Treated With Ozone Comb...mentioning
confidence: 99%
See 3 more Smart Citations
“…As for low NOM-containing ones, the greater the ratio, the better the obtained results (the ratio in the range of 0–0.5) . Considering the problem of residual H 2 O 2 which is recommended to remain lower than 0.5 mg L –1 , Fakioglu et al suggested that the optimal ratio of H 2 O 2 /O 3 was about 0.3 …”
Section: Removal Efficiency Of Odor Compounds Treated With Ozone Comb...mentioning
confidence: 99%
“…Koch et al suggested that the removal rates of odor compounds were independent of the contact time with the oxidizer; 153 these results were contradicted by the work conducted by Fakioglu et al, where removal rates were linearly correlated to the contact time. 154 The determination of the optimal ratio of H 2 O 2 /O 3 is an important problem to be solved in practical applications. For high-NOM source water, the optimal H 2 O 2 /O 3 ratio for eliminating GSM and 2-MIB is about 0.1−0.2.…”
Section: Preozonation In the Drinkingmentioning
confidence: 99%
See 2 more Smart Citations